Temporal evolution of roof collapse from tephra fallout during the 2021-Tajogaite eruption (La Palma, Spain) - Reyes-Hardy, María-Paz; Biass, Sébastien; Dominguez, Lucia; Di Maio, Luigia Sara; Frischknecht, Corine; Bonadonna, Costanza; Pérez, Nemesio (Frontiers in Earth Science, 2024)
Eruptions sustained for weeks to months can exhibit both effusive and explosive styles and associated hazards, and their typically unsteady, pulsatory evolution in time and space result in complex crisis management. Although dominantly effusive, the 2021 Tajogaite eruption from Cumbre Vieja volcano (La Palma, Spain) produced a tephra blanket equivalent to a VEI 3 over 85 days of activity. About one month after the eruption onset, clean-up operations were implemented to mitigate the impact of tephra load on primary buildings. Here, we present a post-event impact assessment of 764 primary buildings, which expands our empirical knowledge of building vulnerability to tephra fallout to include impacts from such long-lasting eruptions causing sustained tephra emission. These field observations are analyzed in the perspective of existing fragility curves, high-resolution satellite imagery and a reconstruction of the spatio-temporal evolution of the tephra blanket to characterize the evolution of roof collapse due to static loads over time. Thanks to a chronological correlation between the temporal evolution of tephra sedimentation and the timing of clean-up operations, we quantified their effectiveness in mitigating roof collapse. If no clean-up measures had been taken, we estimate that 11% of the surveyed buildings would have equalled or surpassed a 75% probability of roof collapse, while only 10 roof collapses have been observed (i.e., 1.3% of the total number of analysed buildings). This work provides key insights for further development of emergency plans for the management of future